POLARIS, SMALL-AMPLITUDE CEPHEID WITH UNIQUE PHYSICAL PECULIARITIES - Usenko, I. A.; Miroshnichenko, A. S.; Klochkova, V. G.; Panchuk, V. E. (Одеські астрономічні публікації, 2017)
We present the results of our analysis of spectroscopic observations of α UMi (Polaris) obtained in 1994 (5 spectra) and 2001-2004 (30 spectra) and frequency analysis of all Polaris RV data collected during last 120 years. This analysis has confirmed the proposition about its overtone pulsations in first and second overtones with P2/P1 = 0.81, i.e. Polaris is double-mode Cepheid (DMC). Moreover, there are the presence of modes splitting for pulsations in these overtones caused by the presence of the three companions at the least with orbital periods of 48.6, 29.91 and 19.44 years, respectively. Since Polaris is located near the blue edges of the Cepheid instability strip for the fundamental mode and first overtone, and an abrupt decrease of the pulsational amplitude and its recent increase could be due to its binarity.